Role of defects and microstructure on the electrical properties of solution-processed Al-doped ZnO transparent conducting films - Kumar A.; Ahmad I. (My University, 2025)
A cheaper, non-vacuum-based routes are required for the large-scale implementation of TCOs in solar cells and LEDs. Generally, solution-based processing routes result in lower transparency and greater resistivity. To achieve electrical conductivity and transparency via solution processing route, greater insight into the effect of processing and microstructure/defects on the electrical and optical properties is needed. In this work, Al-doped ZnO films were deposited on glass substrates by sol–gel spin coating route. The formation of wurtzite structure was confirmed, and the crystallite size of the films was estimated by X-ray diffraction (XRD) pattern analysis. Greater than 85% transparency in the films was obtained in visible and near IR regime as examined by UV–Vis spectroscopy. An increase in the band gap was observed with increasing Al concentration from 0 to 3 at.%. The electrical properties were evaluated by the Hall measurement, and obtained resistivity was in the order of 10–2 Ωcm. The presence of defect states and their co-relation with the electrical properties were investigated by photoluminescence spectroscopy and X-ray photoelectron spectroscopy. © 2020, Springer-Verlag GmbH Germany, part of Springer Nature.